An Economic Agenda for Brazil: Moving forward in the wake of the COVID-19 Pandemic - Ferrari Filho, Fernando (Revista Economia e Políticas Públicas, 2023)
Resumo: Este breve artigo apresenta os efeitos da crise da COVID-19 na economia brasileira, que contribuiu para a “estagnação secular” brasileira no período 2014-2022, descreve as políticas anticíclicas implementadas pelas autoridades econômicas brasileiras para mitigar a crise econômica durante a COVID-19, e propõe uma Agenda Econômica para o terceiro governo Lula da Silva e o período Pós-COVID-19. Palavras- chave: Políticas anticíclicas, Pós-COVID-19 e Agenda Econômica. Abstract:This short article presents the effects of the COVID-19 crisis on the Brazilian economy, that contributed to the Brazilian “secular stagnation” in the period 2014-2022, describes the countercyclical policies implemented by the Brazilian economic authorities to mitigate the economic crisis during the COVID-19, and proposes an Economic Agenda for the Lula da Silva’s third government and the post-COVID-19 period. Key-words: Countercyclical policies, post-COVID-19 and Economic Agenda.